Studi Perbandingan Analisa Struktur Portal Bangunan Menggunakan Software Perhitungan struktur - Fazri, Al-Amin -; Zardi, Muhammad; Amalia, Amalia (Jurnal Teknik Sipil Unaya, 2025)
Building planning must pay attention to strong and economical aspects. By paying attention to these aspects, structural calculations and work implementation must be carried out using SAP 2000 or ETABS. In planning steel structures, planners need to calculate the loads on the building. After the load calculation is carried out, the next step is to carry out structural analysis and planning. This final project aims to make a comparison between SAP 2000 software and ETABS software so as to produce a comparison of the forces produced as well as the forms of modes, moments and movement animations. To make calculations easier and faster, the author uses the spectrum response method with the help of the ETABS and SAP 2000 programs in preparing this final assignment. The reinforcement details from SAP 2000 and ETABS calculations with the reinforcement details from secondary data are the same. From the results of the two applications, there are several differences produced, including in the 5-5 section in the column the axial force is 1.52%, the moment is 2.56% and the shear force is 1.01% with a greater value in the ETABS application. The G-G section in the column the axial force is 1.52%, the moment is 2.56% and the shear force is 1.01% with larger values in the ETABS application.